BIOLOGICAL MANAGEMENT OF EARLY BLIGHT OF POTATO (Journal of Plant Disease Sciences, 2025)
Potato is one of the most well-known vegetables in India. The demand for potatoes is rising because they are nutritious and wholesome, rich in carbohydrates, and contain little fat. Early blight, caused by Alternaria solani and Alternaria alternata, is a widespread disease affecting potato crops globally. The incidence of early blight has been observed extensively in potato-growing areas of Kota district.Chemical control methods are commonly used for managing early blight, but limited work has been done on biological management. Among bio-agents, the results revealed that tuber treatment by spray method with Trichoderma viride @ 8 g/lit per 20 kg, combined with two foliar sprays @ 5 ml/lit of water, was effective against early blight and resulted in better potato yield. This was followed by Pseudomonas fluorescens @ 8 ml/lit per 20 kg of tuber, combined with two foliar sprays @ 5 ml/lit of water, which also showed significant disease control compared to the untreated control.
Keywords: Alternaria alternata; Alternaria solani; Trichoderma viride; Pseudomonas fluorescens